Administrasi Perkara Perdata Secara E-Court di Indonesia - Hisam Ahyani; Muhamad Ghofir Makturidi; Muharir Muharir (Batulis Civil Law Review, 2021)
The purpose of this research is to multiply the innovation related to civil case administration carried out by E-court by the Religious Court of the City of Banjar and the suitability of case administration based on Regulation No.1 of 2019. This research method is included in the category of field research, with a research approach. qualitative, with data collection techniques carried out through observation, interviews, and documentation. Meanwhile, the data analysis technique is done by analyzing the data inductively. The results show that 1) Civil case administration innovation in PA Banjar City in implementing simple, fast and low cost court principles is by implementing E-court, while still monitoring to avoid extortion and brokering perpetrators who charge fees outside the provisions that apply to people who are looking for justice. 2) The suitability of electronic civil case administration carried out in PA Banjar City refers to Perma No. 1 of 2019 can be said to be appropriate, which is evidenced by the existence of communication and socialization to employees, and ecourt services in PA Banjar City are adjusted to SOP which applies to the Banjar City Religious Court. The down payment fee of the case is adjusted to the radius of each area (plaintiff and defendant). 3) Constraints in using E-court in PA Banjar include Server Errors, Human Resources, excessive time saving, unable to explore the information that must be conveyed by both the plaintiff, defendant, and witnesses due to the limited time available the judge.